Analysis of critical thinking skills of junior high school students on vibration and wave materials - Mohammad Tegar Rizky Riezandi; Tutut Nurita (Jurnal Pijar Mipa, 2022)
This research aimed to describe the critical thinking skills of junior high school students on vibration and wave materials. The method used in this research was descriptive quantitative. The subjects in this study were 32 students in the eighth grade of junior high school SMP Negeri 2 Purwosari, Indonesia. The sample consisted of 16 male and 16 female students under the purposive sampling technique. The data collection method used an essay question instrument to test critical thinking skills. The essay question instrument consisted of five indicators of critical thinking skills: giving simple explanations, building basic skills, concluding, making further explanations, and setting strategies and tactics. This research concludes that the average percentage of students' critical thinking skills indicators is 59.94%. The percentage results indicate that the critical thinking skills of students of SMP Negeri 2 Purwosari on vibration and wave materials are classified as less, following the benchmark reference assessment criteria. Based on gender, the results of critical thinking skills between female and male students are relatively the same.